2011
DOI: 10.5713/ajas.2011.11167
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Response to Different Dose Levels of Follicle Stimulating Hormone (FSH) in Different Genotypes of Bangladeshi Cattle

Abstract: The experiment was conducted under the Department of Animal Breeding and Genetics, Bangladesh Agricultural University (BAU), Mymensingh from June, 2001 to December, 2005 in two different locations (Central Cattle Breeding and Dairy Farm and Bangladesh Livestock Research Institute in Savar, Dhaka) to observe ovarian response to different doses of FSH in three different genotypes of cattle- indigenous Local, Pabna cattle and Friesian×Local cross. Five different dose levels used were 200, 240, 280, 320 and 360 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 16 publications
0
10
1
Order By: Relevance
“…However, the types of hormones and its doses were significantly correlated with transferable embryos. Similarly, the recovered embryos and to some extent the ovulation rate showed gonadotropins types and doses-dependent pattern [7,11,33,48]. The ovulation rates continued to increase as FSH doses increased beyond a certain plateau does not done, at the same time fertilization rate and transferable embryo rate remained constant throughout the doses range [7,48,49].…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…However, the types of hormones and its doses were significantly correlated with transferable embryos. Similarly, the recovered embryos and to some extent the ovulation rate showed gonadotropins types and doses-dependent pattern [7,11,33,48]. The ovulation rates continued to increase as FSH doses increased beyond a certain plateau does not done, at the same time fertilization rate and transferable embryo rate remained constant throughout the doses range [7,48,49].…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, the recovered embryos and to some extent the ovulation rate showed gonadotropins types and doses-dependent pattern [7,11,33,48]. The ovulation rates continued to increase as FSH doses increased beyond a certain plateau does not done, at the same time fertilization rate and transferable embryo rate remained constant throughout the doses range [7,48,49]. On other side, some reports have shown there is no effect of gonadotropins doses on embryo quality [50].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The average of corpus luteum in Pesisir cattle after the injection of 16 ml dosage of FSH was 2.97 ± 1.69, whicj was lower than that observed by Nilchuen et al (2012) Bülbül et al(2013) got the CL average 8.4±1.6 on twice a day injection of 400 mg FSH also 150 µg D-cloprostenol together with the fifth FSH induction to Brown Swiss cattle race. Ali et al (2012) reported that in local cattle of Bangladesh the injection of 320 mg FSH gave the best respond on the corpus luteum quantity 13.60±0.51 meanwhile the lowest average is 8.60±0.60 from the quantity of corpus luteum on 200 mg FSH. Abdullah et al (2011) got the CL number of average 2.7±0.7 on 8.8 mg FSH toward Boer goat.…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of reported dataindicates that the effectiveness of the response of the ovaries of embryo donor cows to the exogenous gonadotropin is influenced by many factors [18]. The major are the breed and physiological state of the animals [19,20], especially metabolic [21] and hormonal status [22][23][24][25], genetic predisposition [26][27][28][29][30], ecological and climatic conditions [31,32]. Given the multiplicity of reasons, the ovaries are the most convenient object to predict embryo productivity of a cow [33][34][35].…”
mentioning
confidence: 99%